Perioperative Management of Patient with Esophageal Carcinoma and Crigler-Najjar Syndrome Type 2: A Case Report - Ma, Dehua; Chen, Fang; Chen, Xiaoyun; Chen, Yu (Frontiers in Surgery, 2022)
BACKGROUND Crigler-Najjar syndrome type 2 (CNS-II) is a rare genetic disease that is associated with a lack of uridine diphosphate-glucuronosyltransferase. Esophageal carcinoma is the sixth most common cause of cancer-related death worldwide, for which surgery is the most effective treatment. Reports on patients with both conditions requiring surgery are limited and The impact of hyperbilirubinemia caused by CNS-II on the perioperative period is unknown. Previous studies have found that patients with Crigler-Najjar syndrome have an increased risk of gallstones and related complications, which also poses corresponding challenges to the treatment. Herein, we present a patient with CNS-II who underwent successful thoracoscopic surgery for esophageal carcinoma. CASE SUMMARY A 65-year-old male presented to our hospital with a choking sensation after eating. A physical examination showed yellowing of the sclera and skin. The patient manifested persistent jaundice since birth and had visited many hospitals, but the cause remained undiagnosed. We performed genetic testing, which confirmed CNS-II. Gastroscopy indicated esophageal carcinoma. A multidisciplinary team discussion was carried out to determine the appropriate treatment and perioperative management for this patient. The results show that surgical resection was the most appropriate approach. Finally, the patient underwent thoracoscopic surgery for esophageal carcinoma without complications. CONCLUSION Esophageal carcinoma in patients with Crigler-Najjar syndrome is a rare case, and perioperative management is key in the treatment process. It is necessary to pay close attention to the changes of the disease to prevent complications.